2019
DOI: 10.1016/j.eja.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fungicide treatment and Integrated Pest Management on barley yields: Analysis of a long term field trials database

Abstract: This paper assesses potential for Integrated Pest Management (IPM) techniques to reduce the need for fungicide use without negatively impacting yields. The impacts of three disease management practices of relevance to broad acre crops-disease resistance, forecasting disease pressure, and fungicide use-were analysed to determine impact on yield using a long-term field trials database of Scottish spring barley, with information from experiments across the country regarding yield, disease levels, and fungicide tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Also, the spraying with fungicides had not a clear effect on the barley yield and 1000 kernel weight, and primarily the study year was the main factor that affected barley yield and 1000 kernel weight. As in our study, Stetkiewicz et al, (2019) also concluded that application of fungicide had no effect on barley yield. From the long-term field trials, the application of fungicides resulted in a significant yield increase in only 35% of cases (Stetkiewicz et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Also, the spraying with fungicides had not a clear effect on the barley yield and 1000 kernel weight, and primarily the study year was the main factor that affected barley yield and 1000 kernel weight. As in our study, Stetkiewicz et al, (2019) also concluded that application of fungicide had no effect on barley yield. From the long-term field trials, the application of fungicides resulted in a significant yield increase in only 35% of cases (Stetkiewicz et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…As in our study, Stetkiewicz et al, (2019) also concluded that application of fungicide had no effect on barley yield. From the long-term field trials, the application of fungicides resulted in a significant yield increase in only 35% of cases (Stetkiewicz et al, 2019). On the other hand, in other field trials with spring barley it was shown that the impact of year had a stronger influence on the plant diseases; and spraying of more resistant varieties with fungicides at late growth stage decreased the yield (Sooväli and Koppel, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…However, long-term databases can potentially provide useful information regarding this issue, as data can be collected in a number of weather and agronomic situations, within the same region [28]. In fact, the use of long-term databases has been considered a useful way of teasing apart complex relationships and causality in scientific studies [39,40] despite of their varying levels of quality and consistency [39].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing data collected across a range of sites, in different fields, with different weather conditions, and different management practices, can offer useful insight into which factors are most influential in determining the impact of treatment [28].…”
Section: Methodsmentioning
confidence: 99%
“…is the most frequent and convenient method for achieving effective control during the growing season (Navi, Huynh, Mayers, & Yang, 2019;Stetkiewicz, Burnett, Ennos, & Topp, 2019). However, controlling plant pathogenic bacteria and fungi by chemical substances causes adverse consequences to ecosystems as well as human health (Boudh & Singh, 2019).…”
mentioning
confidence: 99%